Revision of the genus Paraplaneta Warren, 1895 (Lepidoptera: Geometridae, Larentiinae) from Southeast Asia - Choi, Sei-Woong; Stüning, Dieter (Zootaxa, 2011)
The genus Paraplaneta Warren, 1895, until recently treated as a junior synonym of Cataclysme Hübner [1825], is revised. Both genera are members of the tribe Cataclysmini (Herbulot, 1962–63). As a whole, eight species of Paraplaneta are recognized from Himalaya region (India, Pakistan) and China, including four new species: P. anthracica, P. griseobrunnea, P. subfasciata (from China), and P. hreblayi (from Pakistan), described herein. A lectotype for Cataclysme conturbata sternecki Prout, 1938 is designated. Descriptions, diagnoses and illustrations of antennae, wing venation and male and female genitalia of most species are given. The tribal placement of Paraplaneta and related genera within the Cataclysmini is discussed.